Efektivitas Ekstrak Daun Kemangi (Ocimum basilicum L.) terhadap Jumlah Hama Serangga yang Menyerang Tanaman Kacang Hijau (Phaseolus radiatus L.) - Oliska, Serli (Biocaster : Jurnal Kajian Biologi, 2024)
Pests are a type of plant damage that can have fatal consequences for farmers, therefore pests need to be eradicated so that farmers' yields can increase, especially in green bean plants. Basil is one of the biodiversity that has the potential to be developed as a traditional medicine. This plant is a plant that has many benefits as medicine, vegetable pesticide, essential oil producer, vegetable and refreshing drink. This research aims to determine the effectiveness of basil leaf extract (Ocimu basilicum L.) on the number of insect pests that attack green bean plants (Phaseolus radiatus L.). The parameters observed were the number of insect pests before and after treatment. The object of this research was green bean plants, the number of treatments in this research was 4 treatments (0% basil leaf extract, 10% basil leaf extract, 20% basil leaf extract, and 30% basil leaf extract) and 6 replications. Research data is descriptive data. From the research data, it was found that there was a decrease in the number of insect pests before and after treatment in the K3 treatment, the number of insect pests before treatment was 12 and after treatment there were 11 insect pests. In treatment K1-K2 there was no decrease in the number of insect pests before or after treatment. In treatment K1, the number of insect pests before treatment was 9 and after treatment there were 14 insect pests. In the K2 treatment, the number of insect pests before treatment was 12 and after treatment there were 19 insect pests. The results of the study concluded that administering basil leaf extract (Ocimum basilicum L.) had no significant effect on the number of insect pests attacking green bean plants.